A Mist-netting Study of Birds in Lunang Freshwater Swamp Forest, West Sumatra – Part 2 - Wilson Novarino; Richard Noske; Anas Salsabila; Jarulis . (Indonesian Ornithologists’ Union, 2006)
The diversity and guild composition of birds in Lunang freshwater swamp forest, 250 km south of Padang, West Sumatra, was investigated in April-June 2001 using mist nets over 15 days (l 368 net-h) and 20-species list censuses (120 h). A total of 154 individuals belonging to 40 species were captured. Alcedo meninting was the most frequently captured species, followed by Trichastoma rostratum , Macronous gularis, Anthreptes singalensis, and Arachnothera longirostra. Of the nine foraging guilds represented among captured birds, foliagegleaning insectivores were overwhelmingly dominant in terms of both species and individuals. Of 14 families, Timaliidae and Nectariniidae contributed the most to the total number of captured individuals. Including the 70 species recorded only during censuses, 110 species were observed in Lunang swamp forest. Six species were encountered only in mist-nets, indicating the usefulness of this technique in obtaining comprehensive species inventories, especially when experience of calls is limited. Total capture rates were higher than those reported in Peninsular Malaysia and Sarawak, but inter-regional comparisons are constrained by differences in sampling effort, design and habitats.